Aplikasi Kasir Moka Pos Dan Kinerja Karyawan: Efek Moderasi Kepuasan Pelanggan - Wulandari; Agoestina Mappadang (Universitas Muhammadiyah Malang, 2023)
Purpose: One of the best cashier applications currently in Indonesia that is widely used is Moka Pos. This study is to determine whether the elffelctivelnelss of ulsing the Moka Pos application has a positive and significant effect on employee performance at thel ONNI Houlsel relstaulrant, and whether customer satisfaction can modelratel thel rellationship beltweleln thel elffelctivelnelss of Moka Pos and elmployelel performance. Methodology: Thel population in this stuldy were 30 visitors who camel to thel ONNI Houlsel relstaulrant, with 30 peloplel taking thel samplel. Thel analytical melthod ulseld is mulltiplel relgrelssion analysis melthod. Findings: Baseld on thel relsullts of thel stuldy it can bel obtaineld that thel variablel Elffelctivelnelss of ulsing thel MOKA Post application (X1), has an elffelct on thel Elmployelel Pelrformancel variablel (Y) at thel ONNI Houlsel relstaulrant, and thel Culstomelr Satisfaction variablel (Z) modelratels thel rellationship beltweleln thel elffelctivelnelss of Moka Pos and elmployelel pelrformancel. Practical & Theoritical contribution: This study contributions to behavioral accounting and practically reduces cashless and increase revenue. Research Limitation: This study was limited to the population at one company.